معوقات تطبيق الإدارة الإلكترونية للموارد البشرية في المؤسسات التعليمية (دراسة ميدانيّة في جامعة تشرين) - تركمان, حنان; خليل, علاء (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف البحث إلى التعرف على معوقات تطبيق الإدارة الإلكترونية للموارد البشرية في جامعة تشرين، ويركّز الباحث على المعوقات الإدارية والبشرية، حيث أنَّ هناك العديد من العوامل الإدارية والبشرية التي تقف عقبةً في وجه تطبيق هذا النهج الإداري الحديث من حيث المفهوم والوظائف ومقومات التطبيق. واعتمد الباحث على المقاربة الاستنباطية والمنهج الوصفي كمنهج عام للبحث، وقام الباحث بتوزيع 60 استبياناً على العاملين في مديرية شؤون الموظفين في جامعة تشرين، وخلصت الدراسة إلى وجود العديد من المعوقات الإدارية والبشرية وأبرز هذه المعوقات الإجراءات الروتينية والمعقدة والمركزية الشديدة وقلة التحفيز المادي والمعنوي وضعف البرامج التدريبية. وقدم الباحث العديد من التوصيات أهمهما تبسيط الإجراءات الإدارية وتحفيز العنصر البشري لاستخدام التكنولوجيا. This research aimed to identify obstacles of implementing electronic human resource management(E-HRM), and researcher will concentrate on managerial and human obstacles. Where there are many administrative and human factors that stand obstacle to the application of the new management approach in terms of concept and functions and elements of the application. The researcher relied on the Deductive Approach and on the descriptive approach as a general method for research. The researcher distributed a questionnaire to 60 employees in the Directorate of Personnel Management at Tishreen University. The study concluded that there are many administrative and human obstacles, highlighted these constraints routine and complex procedures and the centralization, lack of material and moral stimulation and poor training programs. The researcher presented many of the most important recommendations which are simplifying administrative procedures and motivate the human element to the use of technology.